Curcumin Inhibits Tumor Growth and Angiogenesis in an Orthotopic Mouse Model of Human Pancreatic Cancer. (10th November 2013) - Bimonte, Sabrina; Barbieri, Antonio; Palma, Giuseppe; Luciano, Antonio; Rea, Domenica; Arra, Claudio
Abstract : Pancreatic cancer is a malignant neoplasm originating from transformed cells arising in tissues forming the pancreas. The best chemotherapeutic agent used to treat pancreatic cancer is the gemcitabine. However, gemcitabine treatment is associated with many side effects. Thus novel strategies involving less toxic agents for treatment of pancreatic cancer are necessary. Curcumin is one such agent that inhibits the proliferation and angiogenesis of a wide variety of tumor cells, through the modulation of many cell signalling pathways. In this study, we investigated whether curcumin plays antitumor effects in MIA PaCa-2 cells. In vitro studies showed that curcumin inhibits the proliferation and enhances apoptosis of MIA PaCa-2 cells. To test whether the antitumor activity of curcumin is also observed in vivo, we generated an orthotopic mouse model of pancreatic cancer by injection of MIA PaCa-2 cells in nude mice. We placed mice on diet containing curcumin at 0.6% for 6 weeks. In these treated mice tumors were smaller with respect to controls and showed a downregulation of the transcription nuclear factor NF- κ B and NF- κ B-regulated gene products. Overall, our data indicate that curcumin has a great potential in treatment of human pancreatic cancer through the modulation of NF- κ B pathway.